The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/ausal-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and flesh colour differences in grafted and non-grafted watermelon

Abstract: Abstract. The experiment was carried out in three regions in Hungary (Jászszentandrás, Cece,Újkígyós) in 2013 to determine the fruit quality of grafted watermelon (Citrullus lanatus Thunb.). The "RX 467" seedless watermelon variety was grafted on two commercial rootstocks "FR STRONG" [Lagenaria siceraria (Mol.) Standl.] and "RS 841" (Cucurbita maxima Duchesne × Cucurbita moschata Duchesne). The lycopene and flesh colours are important quality characteristics even of the selfrooted and grafted watermelon. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Grafting is used widely with tomato and watermelon to improve water and mineral nutrition of plants, enhance the tolerance to soil-borne diseases (e.g., fusarium wilt) and abiotic stress, as well as to increase yield and fruit quality (Kyriacou et al, 2017). Complex interactions between rootstock type, growing season, salinity, and genotype on carotenoid concentration, particularly lycopene, have been reported in both vegetable crops, leading to conflicting results (Fekete et al, 2015; Marsic et al, 2018).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 99%
“…Grafting is used widely with tomato and watermelon to improve water and mineral nutrition of plants, enhance the tolerance to soil-borne diseases (e.g., fusarium wilt) and abiotic stress, as well as to increase yield and fruit quality (Kyriacou et al, 2017). Complex interactions between rootstock type, growing season, salinity, and genotype on carotenoid concentration, particularly lycopene, have been reported in both vegetable crops, leading to conflicting results (Fekete et al, 2015; Marsic et al, 2018).…”
Section: Carotenoid In Tomato and Watermelon Fruitsmentioning
confidence: 99%
“…Our study is compatible with the results of Petropoulos et al (2014) reporting that fruit flesh color mostly depended on the rootstock-scion combination. Fekete et al (2015) informed us that L* value varied from 35.17 to 42.71; C* value 31.59 to 38.41; h angle 33.42 to 36.13, and that while interspecific grafting decreased h angle value, it increased C* value.…”
Section: Pulp Colorimetrymentioning
confidence: 83%
“…Bruton et al (2009) reported that lycopene content for watermelons ranged from 43.6 to 78.9 µg/g. Fekete et al (2015) reported that interspecific hybrid rootstocks (C. maxima x C. moschata) increased the lycopene contents of watermelons. Contrary to the above-mentioned researcher, Turhan et al (2012) didn't observe any differences in watermelon lycopene content for grafted and ungrafted plants.…”
Section: Lycopenementioning
confidence: 99%